Multi-key homomorphic proxy re-encryption scheme based on NTRU and its application - Ruiqi LI; Chunfu JIA; Yafei WANG (Tongxin xuebao, 2021)
To improve the practicability of homomorphic encryption in the application of multi-user cloud computing, a NTRU-based multi-key homomorphic proxy re-encryption (MKH-PRE) scheme was constructed.Firstly, a new form of NTRU-based multi-key ciphertext was proposed based on the idea of ciphertext extension, and the corresponding homomorphic operations and relinearization procedure were designed on the basis of this new ciphertext form, so that a NTRU-based multi-key homomorphic encryption (MKHE) scheme which supported distributed decryption was constructed.Then, resorting to the idea of key switching, the re-encryption key and re-encryption procedure were put forward such that the functionality of proxy re-encryption (PRE) was integrated to this new NTRU-based MKHE scheme.The MKH-PRE scheme preserved the properties of MKHE and PRE, and had a better performance on the client side.The scheme was applied to the privacy-preserving problems in federated learning and an experiment of the application was carried out.The results demonstrate that the accuracy of learning is scarcely affected by the encryption procedure and the computational overhead of this MKH-PRE scheme is acceptable.